Gratitude, gifts and emotions in the struggle for the land of a rural social movement - Pena, Mariela (2019)
This work explores the praxis of gratitude category in different spheres of political action. A promising approach to the subjective motives and to the affective nature that, as has already been revealed by social sciences, through the so-called affective turn, conform behaviors related to political life (Ahmed, 2004). Specifically, this study is proposed as a theoretical reflection anchored in a concrete empirical case. It takes as a reference the Rural Movement of Santiago del Estero-Vía Campesina (MOCASE-VC), a social movement in the north-central region of Argentina, consisting of rural marginalized people, which by now has a 28-year history of political life. This organization, which initially aimed to act as a trade union and to offer legal advice regarding conflicts with business sectors on land possession and ownership, later became a social movement as a response to contemporary capitalism’s way of life.